PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI PADA BADAN PUSAT STATISTIK (BPS) PROVINSI MALUKU - Rosana Ana Marin Siahaya; Mohamad Arsad Rahawarin; Julia Theresia Patty (Social and Political Sciences Faculty, Widya Gama Mahakam Samarinda University, 2025)
Transformational leadership plays an important role in improving organizational performance by creating an inspiring vision, building strong working relationships, and encouraging innovation. This study aims to analyze the impact of transformational leadership on employee performance across various sectors, with a focus on the Central Bureau of Statistics (BPS) in Maluku Province. The research employs a quantitative approach and is analyzed using statistical methods. The findings show that transformational leadership has a positive impact on employee motivation, engagement, and productivity. Leaders who provide a clear vision, offer emotional support, and encourage innovation have been proven to enhance organizational effectiveness. This study also identifies challenges in implementing transformational leadership, such as resistance to change and resource constraints. Therefore, it is crucial for organizations to develop adaptive and sustainable leadership strategies to optimize employee performance. These findings are expected to serve as a reference for stakeholders in designing more effective leadership policies.